2018
DOI: 10.1186/s40792-018-0521-5
|View full text |Cite
|
Sign up to set email alerts
|

Microlaryngoscopic surgery for pyriform sinus fistulas in children: a report of two cases

Abstract: BackgroundA pyriform sinus fistula (PSF) is a rare branchial anomaly that causes recurrent cervical infections. Open neck surgery has widely been accepted as a definitive treatment for PSFs, and endoscopic surgery has been reported in recent years. However, both approaches are not satisfactory because of high recurrence rates and postoperative complications. Microlaryngoscopic surgery (MLS) is a transoral surgical technique involving the use of an operating microscope. In this report, we present a new procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…While Kamide et al 20 and Koyama 21 reported that the normal hypopharyngeal mucosa was sutured following fistula resection. Nomura et al 22 also reported 2 fistulas were securely sutured using absorbable suture material under microlaryngoscopic surgery. Our double suture could increase the thickness of mucosa in order to enhance wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…While Kamide et al 20 and Koyama 21 reported that the normal hypopharyngeal mucosa was sutured following fistula resection. Nomura et al 22 also reported 2 fistulas were securely sutured using absorbable suture material under microlaryngoscopic surgery. Our double suture could increase the thickness of mucosa in order to enhance wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of technology and popularization of minimally invasive surgery, endoscopic surgery is less invasive and exhibits a better cosmetic effect compared with open neck surgery. A few reports have advocated electrocautery, chemical cautery, and other strategies for the treatment of CPSF [5,6], which are less invasive and hardly produce a cutaneous scar. Nevertheless, these methods are imperfect so far, as their recurrent rates are higher than the complete resection approach [19].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrent infection and previous surgery usually destroy the surrounding normal anatomies, making it dangerous to eradicate the tract [2,3]. Over the past few years, there has been increasing interest in treating CPSF using endoscopic obliteration or cauterization as the primary treatment [5,6], and hence, open surgery is no longer compulsory. However, in some cases, relapses are unavoidable due to incomplete closure of the tract opening and/or remainder of the fistula epithelial lining.…”
Section: Introductionmentioning
confidence: 99%
“…At present, complete resection of fistula is still the most common and thorough treatment for PSF (1,2,6,15,16). However, in a review of 177 published reports on PSF, 377 patients who underwent open surgery, 15% recurrence occurred after initial surgery, the same as under endoscopic cauterization.…”
Section: Endoscopy Collaborationmentioning
confidence: 99%
“…Radical resection of fistula after resolution of inflammation is the key to avoid recurrence. However, it is difficult to find the fistula in traditional open-neck surgery, or the resection is incomplete, which may lead to recurrence (1,6). In recent years, minimally invasive endoscopic occlusion of the internal opening for the treatment of PSF is performed, including biocauterization (7), electrocautery (8), chemocautery (9), coblation (10), laser cauterization (11), and suture closure (6), etc.…”
Section: Introductionmentioning
confidence: 99%